2015
DOI: 10.1146/annurev-fluid-010814-014720
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence of Drops

Abstract: This review examines different stages of the coalescence process of liquid drops on a planar interface under different conditions. Depending on the application, drops coalescence under the influence of applied external shear stress. The focus of this review is on the effect of the viscous stress, Marangoni stress, and electric field stress on the outcome of this process, particularly on the time of coalescence and partial coalescence. Theoretical progress and experiments of this phenomenon are examined, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
104
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 136 publications
5
104
1
Order By: Relevance
“…In the literature, there is no general consensus on whether the viscosity of the drop or of the surrounding liquid is more important for partial coalescence and different forms of the Oh number have been suggested. Investigators have used the higher of the two viscosities, 22 or the viscosity of the drop phase only, 8,13,17 to calculate the Oh number, or have considered more than one Oh numbers based on the drop liquid Oh d and on the surrounding liquid Oh s . 9,19 According to Kinoshita, Teng, and Masutani, 18 the viscosity of the droplet is more important in partial coalescence, and this will be used subsequently for the estimation of the Oh number.…”
Section: A Boundary Between Partial and Total Coalescencementioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there is no general consensus on whether the viscosity of the drop or of the surrounding liquid is more important for partial coalescence and different forms of the Oh number have been suggested. Investigators have used the higher of the two viscosities, 22 or the viscosity of the drop phase only, 8,13,17 to calculate the Oh number, or have considered more than one Oh numbers based on the drop liquid Oh d and on the surrounding liquid Oh s . 9,19 According to Kinoshita, Teng, and Masutani, 18 the viscosity of the droplet is more important in partial coalescence, and this will be used subsequently for the estimation of the Oh number.…”
Section: A Boundary Between Partial and Total Coalescencementioning
confidence: 99%
“…The ratio was found to be equal to ξ = (2Z 2 0 /3) 1/3 , where Z 0 is a non-dimensional parameter which represents the ratio of the wavelength of disturbance to the diameter of the liquid column. 21 Recently, Kavehpour 22 suggested that ξ = (1 3…”
Section: Introductionmentioning
confidence: 99%
“…Charles & Mason 1960a,b;Jeffreys & Davis 1971), leading to a classification of different dynamical regimes (Aryafar & Kavehpour 2006 in high-speed imaging (Thoroddsen & Takehara 2000), experimental techniques (Mohamed-Kassim & Longmire 2004), and numerical simulations (Blanchette & Bigioni 2006) have furthered our understanding of coalescence in various circumstances, including the effects of concentration-induced Marangoni stresses (Blanchette, Messio & Bush 2009). The myriad aspects of coalescence were recently reviewed by Kavehpour (2015).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in a multiphase flow context the dynamics of bubbles and droplets including their deformation, coalescence and breakup are intriguing processes which have gained a lot of attention in the scientific community, cf. [4,6,21,23,24]. In two-phase flows, being the most common multiphase flow configuration involving two distinct fluids, the fluids are segregated by a very thin interfacial region where surface tension effects and mass transfer due to chemical reactions may appear.…”
Section: Introductionmentioning
confidence: 99%